PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) BERBANTUAN VIDEO YABUTIN TERHADAP PEMAHAMAN KONSEP DAN KOLABORASI SISWA SD - Listyaningtyas, Evi; Yuni Purwanti, Kartika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of conceptual understanding and suboptimal collaboration among fourth-grade students at Pagersari 02 Public Elementary School, which was attributed to the lack of variety in teaching models and learning media. The study aimed to determine the differences and effects of the Team Games Tournament (TGT) learning model supplemented with the Yabutin video on students’ conceptual understanding and collaboration. The research method employed a quantitative approach with a quasi-experimental nonequivalent control group design. The research sample consisted of Class IVB as the experimental group and Class IVA as the control group, selected through purposive sampling. Data collection utilized a concept comprehension test and a questionnaire to measure collaboration. Data analysis techniques included the independent samples t-test and regression analysis. The results of the data analysis indicate that (1) There is a difference in conceptual understanding and collaboration. This is evidenced by the results of the independent samples t-test. (2) The results of the simple linear regression test indicate that the application of the TGT model supported by video has a significant effect on conceptual understanding and collaboration. The experimental class achieved significantly higher posttest scores compared to the control class. In conclusion, the use of the video-assisted TGT model by Yabutin enhances students’ conceptual understanding and collaboration skills.